Sustained delivery of the bone morphogenetic proteins BMP-2 and BMP-7 for cartilage repair and regeneration in osteoarthritis - Whitty, Ciara; Pernstich, Christian; Marris, Charlotte; McCaskie, Andrew; Jones, Michael; Henson, Frances (Osteoarthritis and cartilage open, 2022)
Attempts to utilise growth factors (GF) such as bone morphogenic proteins (BMPs) to treat osteoarthritis (OA) in the clinic have not secured widespread adoption. However, the novel crystalline GF formulation called PODS offers new perspectives. This study investigated the hypothesis that Polyhedrin Delivery System (PODS) BMP-2 and PODS BMP-7, compared with conventional BMP-2 and BMP-7 increase capacity for cartilage repair. Sustained release from PODS BMP-2 and PODS BMP-7 and their effects on OA patient-derived cells as well as a chondrocyte cell line were first assessed in vitro. Here, extra cellular matrix (ECM) protein gene expression and actual ECM deposition were measured and compared to the effect achieved with conventional, soluble BMPs. Subsequently, in an established murine model of cartilage regeneration of the knee joint, changes were traced over 8 weeks and scored with two metrics, modified Pineda and Mankin. Both crystalline PODS BMP formulations strongly induced proliferation in primary as well as immortal cell line chondrocytes, outperforming conventional soluble BMP-2 and BMP-7. Furthermore, ECM-producing genes were upregulated and the production of ECM could be demonstrated. In the murine cartilage regeneration model, both PODS BMP-2 and PODS-BMP-7 improved cartilage repair assessed with both histological scoring methods. This study showed that the sustained release of GF from PODS BMPs is effective in promoting chondrogenesis in vitro. The small animal data suggests that this novel approach of delivering therapeutic proteins sustainably and locally to the knee has promise for developing future disease-modifying therapies of OA.